Tides and Volcanoes: A Historical Perspective - Sottili, Gianluca; Lambert, Sebastien; Palladino, Danilo Mauro (Frontiers in Earth Science, 2021)
We examine the origins and the history of the hypothesis for an influence of tidal forces on volcanic activity. The idea of an influence of the Moon and Sun on magmatic processes dates back to the Hellenistic world. However, it was only since the late 19th century, with the establishment of volcano observatories at Mt. Etna and Vesuvius allowing a systematic collection of observations with modern methods, that the “tidal controversy” opened one of the longest and most important debates in Earth Science. At the beginning of the 20th century, the controversy assumed a much more general significance, as the debate around the tidal influence on volcanism developed around the formulation of the first modern theories on the origins of volcanism, the structure of the Earth’s interior and the mechanisms for continental drift. During the same period, the first experimental evidence for the existence of the Earth tides by Hecker (1907), and the Chamberlin–Moulton planetesimal hypothesis (proposed in 1905 by geologist T.C Chamberlin and astronomer F.R Moulton) about the ‘tidal’ origin of the Solar System, influenced and stimulated new researches on volcano-tides interactions, such as the first description of the ‘lava tide’ at the Kilauea volcano by T.A Jaggar in 1924. Surprisingly, this phase of gradual acceptance of the tidal hypothesis was followed by a period of lapse between 1930 to late 1960. A new era of stimulating and interesting speculations opened at the beginning of the seventies of the 20th century thanks to the discovery of the moonquakes revealed by the Apollo Lunar Surface Experiment Package. A few years later, in 1979, the intense volcanism on the Jupiter’s moon Io, discovered by the Voyager 1 mission, was explained by the tidal heating produced by the Io’s orbital eccentricity. Lastly, we discuss the major advances over the last decades and the new frontiers of this research topic, which traditionally bears on interdisciplinary contributions (e.g., from geosciences, physics, astronomy). We conclude that the present-day debate around the environmental crisis stimulated a new field of research around the complex mechanisms of mutual interactions among orbital factors, Milankovitch Cycles, climate changes and volcanism.